The Effectiveness of Ascidian Didemnum molle Extracts as Antibactery Vibrio harveyi on Tiger Shrimp (Penaeus monodon) - Christin Jelita, Christin Jelita; Bachtiar, Eri; Liviawaty, Evi (Aquacultura Indonesiana, 2014)
This research studied the effectiveness of Ascidian Didemnum molle extracts as curative for bacteria Vibrio harveyi infection in tiger shrimp (Penaeus monodon). The purpose of the research was to find out the effective concentration of antibacterial compound Ascidians Didemnum molle to curative the infection of bacteria Vibrio harveyi in tiger shrimp. The Ascidians Didemnum molle which were used in this research was originated from Kepulauan Seribu waters. Ascidians Didemnum molle collected by 3.5 kg with an average size of 5-15 cm per individual. The research was conducted from September to December 2013 at the Biotechnology Laboratory and Aquaculture Laboratory of the Faculty of Fisheries and Marine Sciences, Padjadjaran University. The method which was used in this research was a laboratory experimental method such as phytochemical test, extraction, anti-Vibrio harveyi activity test, LC50 test and chalenge test. Descriptive analysis was used in this research. Based on the anti-Vibrio harveyi activity test, it could be concluded that Ascidian Didemnum molle extract had potential as an antibacterial for Vibrio harveyi, which indicated by inhibition zones as 11.1 mm at a concentration of 1,000 mg/L. The result of EPA Probit analysis on LC50 test, with 48-hours of observation, determine 387 mg/L as a safe extract concentration for tiger shrimp. The chalenge test showed that treatment D with concentration of 290.25 mg/L was effective to be used as treatment for tiger shrimp that were infected by Vibrio harveyi bacteria solution of density 106 CFU/ mL, with the highest survival rate was 51.7%.